2021
DOI: 10.3390/epigenomes5040022
|View full text |Cite
|
Sign up to set email alerts
|

One Omics Approach Does Not Rule Them All: The Metabolome and the Epigenome Join Forces in Haematological Malignancies

Abstract: Aberrant DNA methylation, dysregulation of chromatin-modifying enzymes, and microRNAs (miRNAs) play a crucial role in haematological malignancies. These epimutations, with an impact on chromatin accessibility and transcriptional output, are often associated with genomic instability and the emergence of drug resistance, disease progression, and poor survival. In order to exert their functions, epigenetic enzymes utilize cellular metabolites as co-factors and are highly dependent on their availability. By affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 375 publications
(446 reference statements)
0
4
0
Order By: Relevance
“…We and others have previously demonstrated the clinical relevance of targeting PRC2 in MM and that PRC2-mediated gene silencing is a key feature of MM pathogenesis. 2 , 3 One challenging aspect of defining target genes of PRC2 is that this complex lacks sequence specificity; thus, the molecular mechanisms of its genomic localization are largely unknown. Prior studies have suggested that EZH2-lncRNA interactions could promote PRC2’s functional capacity to bind chromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously demonstrated the clinical relevance of targeting PRC2 in MM and that PRC2-mediated gene silencing is a key feature of MM pathogenesis. 2 , 3 One challenging aspect of defining target genes of PRC2 is that this complex lacks sequence specificity; thus, the molecular mechanisms of its genomic localization are largely unknown. Prior studies have suggested that EZH2-lncRNA interactions could promote PRC2’s functional capacity to bind chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Global multi-omics analyses have revealed that MM cells exhibit complex intra-tumoral heterogeneity, have a diverse mutational landscape and undergo large scale epigenetic and metabolic reconfiguration during disease progression. 2 , 3 As a result, patients undergoing conventional treatment eventually develop drug resistance and relapse in disease. 4 In recent years, we and others have presented data suggesting that epigenetic regulatory mechanisms are key features in MM pathogenesis, and numerous drugs targeting epigenetic regulators have been developed and tested clinically or preclinically.…”
Section: Introductionmentioning
confidence: 99%
“…This process is catalysed by the DNA methyltransferases, DNMT1 and DNMT3A/B and can be reversed by the DNA demethylase enzymes TET1-3 ( 41 ). Disrupted DNA methylation has been shown to promote carcinogenesis and disease progression in multiple cancers ( 3 , 42 , 43 ). In fact, it has previously been suggested that promoter DNA hypermethylation is accountable for decreased expression of 35 lncRNAs in hepatocellular carcinoma ( 40 , 44 ).…”
Section: The Functional Impact Of Lncrnas In Epigenetic Regulationmentioning
confidence: 99%
“…Although, data is largely lacking how regulation of lncRNAs by the deposition of histone modifications may directly influence their expression, there is now emerging data indicating that lncRNAs may act as recruiters, guides and scaffolds for protein complexes including chromatin modifiers, thus epigenetically influencing the expression of other genes. Prior studies have shown that PRC2-mediated gene silencing is important for MM pathogenesis and disease progression, both in vivo and in vitro ( 7 , 8 , 10 , 43 ). Furthermore, several lncRNAs have been suggested to regulate the enzymatic activity of PRC2 by binding to the catalytic subunit EZH2.…”
Section: The Functional Impact Of Lncrnas In Epigenetic Regulationmentioning
confidence: 99%